Manajemen Penerimaan Peserta Didik Baru: Studi Kasus MIN 7 Boyolali - Badriyah, Siti; Supriyanto, Supriyanto (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
This study aims to determine the planning, implementation, and evaluation of new student admissions at MIN 7 Boyolali, as well as the supporting and inhibiting factors. The research method used is qualitative case study method. Data collection techniques are done by interview, observation, and documentation. Data analysis techniques with data reduction, data presentation, and conclusion drawing/verification. The results showed that the management of new student admissions at MIN 7 Boyolali showed positive results. Through careful planning, effective implementation, and continuous evaluation, MIN 7 Boyolali succeeds in increasing the number of new student admissions each year. Supporting factors such as visionary leadership, cooperation with external parties, and community support, play a vital role in the success of PPDB management. However, inhibiting factors such as limited resources and changes in the external environment need to be addressed appropriately so that MIN 7 Boyolali can continue to develop as a superior Islamic education institution that is in demand by the community.